Dynamics of urban development patterns on thermal distributions and their implications on water spread areas of Vellore, Tamil Nadu, India - Manjunath, D. R.; Jagadeesh, P. (Frontiers in Sustainable Cities, 2024)
Recent satellite maps reported that India is experiencing extreme heat waves, surpassing Middle Eastern countries. This study addresses a critical gap in understanding how land use land cover (LULC) changes impact on land surface temperature (LST), urban heat intensity (UHI) and water spread area (WSA) in rapidly growing cities like Vellore and Katpadi across three decades . We used Landsat thermal bands and support vector machine (SVM) algorithm to investigate LULC and LST patterns to understand the impacts of urbanization and water body reduction impact on local climate dynamics. LULC results showed an increase in built-up lands from 5.89% to 25.89% and further zooming water area decreased from 3.15% to 1.02%. LST showed a significant increasing trend for water bodies and vegetation ranging from 17.4°C to 26°C, barren and built-up areas ranging from 28°C to 42.6°C. The multivariate analysis revealed a positive correlation between LST and normalised difference built-up index (NDBI) and negative correlations between LST and normalised difference vegetation index (NDVI), normalised difference water index (NDWI), and modified normalised difference water index (MNDWI). Moreover, spatial and time series analysis in WSAs reveals a significant positive trend in LST. Further, a strong negative correlation observed between WSA and LST. Investigations reported that a 10% decrease in WSA could lead to an increase in the LST of 0.12°C to 0.55°C in surrounding regions. Current study contributes to improve land use policy and management of lakes in urban areas and environmental concerns, highlighting the need to mitigate heat impacts and manage water resources in rapidly growing cities. Our results provide valuable insights for policymakers and practitioners seeking to create more sustainable, resilient, and livable urban environments.